Organizational citizenship behavior in the inspectorate of banjarmasin city government: the role of organizational commitment and job satisfaction - Firdaus Firdaus; Syahrial Shaddiq (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The role of organizational commitment and job satisfaction is very important in a healthy and productive work environment. Both are interrelated and can affect individual, group, and organizational performance. So therefore, need to be evaluated how organizational commitment (OC), job satisfaction (JS), and organizational citizenship behavior (OCB) in the government sector, namely the Inspectorate of Banjarmasin City Government. This research takes a quantitative approach with explanatory analysis. This results research is expected to add to the literature on organizational commitment, job satisfaction, and employee OCB. Based on the results of the study, organizational commitment (OC), and job satisfaction (JS) had a positive and significant effect on organizational citizenship behavior (OCB) at the Inspectorate of the Banjarmasin City Government, both partially and simultaneously. This study provides recommendations Organizations can focus on fostering a positive work environment that encourages commitment and satisfaction. Employees who are committed and satisfied are more likely to stay with the organization and contribute positively over the long term. Managers can use insights from this relationship to develop strategies that promote commitment and job satisfaction